Honesty Education For Children From a Very Early Age: An Islamic Perspective On Psychology - Adi Heryadi; Subandi Subandi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
The phenomena of corruption, collusion, and nepotism in Indonesia that are increasingly prevalent have made deep works for us as a nation. We can see the bad behavior of corruption, starting from the suboptimal quality of development results to the increasingly visible impact between the rich and the poor. People's dissatisfaction with the spectacle of corruption trials and terrible examples set by the nation's leaders has a psychological effect on the next generation. According to (Suud & Subandi, 2017), one of the repercussions of dishonesty is corruption. From the perspective of Islamic psychology, this study tries to answer research issues concerning what and how to undertake moral education for children. A library research or literature review is used in this study, as well as a non-interactive method called document analysis. Researchers consult a variety of sources, including documents, books, websites, study findings, and expert opinions, that are relevant to the research issue. The findings of this study show that, according to Islamic psychology, honesty education for children is a type of moral character education that teaches children aged 0 to 6 years how to coordinate their hearts and brains through words and actions. They always say that the Qur'an and Hadith are the most reliable guides. Furthermore, the stages of children's integrity character education discovered in Islamic psychology are the conception period, the first three years, and the 46th year, which are key moments in integrity character education. That will be in 46 years. The basic foundations for this performance are Surah an-Nahl: 78 and Surah an-Nisa: 5.